Learning Angular : LiveLessons - Wandschneider, Marc; Safari eBooks ([Place of publication not identified] : Pearson, 2018)
"Angular is a powerful JavaScript framework, maintained by Google, for building web applications and for enhancing various parts of your web pages. It's a comprehensive framework that makes both development and testing easier by extending web applications with MVC capability. Marc Wandschneider, senior developer advocate at Google, has more than 20 years of experience as a developer and is the author of two programming books and two other LiveLessons video training. In this video training, Marc uses a live-coding approach throughout to show developers how to start from scratch and work their way up to building a meaningful, yet not overly complicated application. In this video training, Marc starts by introducing Angular and showing how to install it along with related tools like Node.js, TypeScript, Bootstrap, Angular CLI, and Visual Studio Code. After a quick tutorial on TypeScript, the video course next shows how to create an Angular application from scratch while explaining the primary pieces of an Angular application and see how they work together. Using lots of examples, the core parts of Angular are introduced, such as Components, Directives, the Router, Services, and Pipes and Directives."--Resource description page.
Presenter, Marc Wandschneider.
Title from title screen (viewed January 23, 2018).
Keywords: Web site development; Web sites -- Design; JavaScript (Computer program language); Client/server computing; Electronic books